Pendekatan Reciprocal Teaching Berbantuan Wondershare Quiz Creator Pada Pembelajaran Matematika - Lala Anggraini; Achmad Hidayatullah; Endang Suprapti (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2020)
This research describes and elaborates on the effect of Reciprocal Teaching assisted Wondershare Quiz Creator media to Mathematics learning outcome in the VIII.B class students of SMP Muhammadiyah 13 Surabaya. This research was conducted to enhance students' mathematics outcomes by using True Experimental research design with Pretest-Post-test Control Group Design. The collecting data technique used to pretest and post-test also students' and teachers' activity observation worksheet and students’ response questionnaire; all the instruments were analyzed using descriptive quantitative. The results show (1) based on t-test measurement, it is found that the average of the final score of the experimental group is better than the control group; (2) the most dominant on students’ activity is participating in problem-solving activities by discussing with groups with the result of 37%; (3) teachers activities score an average of 3.72 which means very good; (4) students indicate positive respond on learning with a score of 95.6%. So, it can be concluded that the reciprocal teaching approach assisted the wonder-share quiz creator which has a positive and significant effect.